2014
DOI: 10.1162/jocn_a_00549
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Structural Correlates of Cognitive Control during Adolescent Development: A 4-Year Longitudinal Study

Abstract: Maturation of cognitive control abilities has been attributed to the protracted structural maturation of underlying neural correlates during adolescence. This study examined the relationship between development of two forms of cognitive control (proactive and reactive control) and structural maturation of the ACC, dorsolateral pFC, and ventrolateral pFC (vlPFC) between early and mid adolescence using a longitudinal design. Adolescents (n = 92) underwent baseline assessments when they were 12 years old and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…This structure has also been implicated in intentional causality; referring to causal links between one's own intentions and actions (Den Ouden, Frith, Frith, & Blakemore, ), which also may be essential for planning and execution of goal‐directed behavior. Additionally, longitudinal studies on adolescents have related superior performance in cognitive control (Vijayakumar, Whittle, Yücel, et al., ), a concept related to conscientiousness (Fleming, Heintzelman, & Bartholow, ), to greater cortical thinning of the right anterior cingulate cortex. Finally, imagination, the only personality trait consistently associated with measures of intelligence (DeYoung & Gray, ), was negatively related to the CT change in the right postcentral gyrus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This structure has also been implicated in intentional causality; referring to causal links between one's own intentions and actions (Den Ouden, Frith, Frith, & Blakemore, ), which also may be essential for planning and execution of goal‐directed behavior. Additionally, longitudinal studies on adolescents have related superior performance in cognitive control (Vijayakumar, Whittle, Yücel, et al., ), a concept related to conscientiousness (Fleming, Heintzelman, & Bartholow, ), to greater cortical thinning of the right anterior cingulate cortex. Finally, imagination, the only personality trait consistently associated with measures of intelligence (DeYoung & Gray, ), was negatively related to the CT change in the right postcentral gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to conclude that exaggeration of the patterns associated with normative brain structural development is adaptive. Although some studies lend support to this notion (Dennison et al., ), others (Vijayakumar, Whittle, Yücel, et al., ) point out that specific patterns of cortical development, for example, increases or decreases in CT in particular periods, may be related to specific developmental outcomes. Indeed timing, for example, delays rather than complete deviation from normal cortical development may be crucial for developmental outcomes (Ducharme et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although different scanners were used at Time 1 versus Times 2 and 3, our previous work has shown no inter‐scanner bias [Vijayakumar et al, ; Whittle et al, ]. However, to fully address any concerns that changes in cortical metrics over time may be due to measurement bias from the different scanner platforms and acquisition parameters, a reliability analysis was undertaken using four individuals who were scanned on both BRI and RCH scanners over a time interval of 1–2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a population study examining the related construct of IQ across the ages 7, 9, 11, and 13 years reported that “in a nontrivial minority of children, naturalistic IQ change is marked and real, but this change is variable in its timing, idiosyncratic in its source and transient in its course (Page 444)” (Moffitt, Caspi, Harkness, & Silva, ). Neuroimaging studies in adolescents also suggest that the development of executive functions, including working memory, may include developmental spurts, deceleration, and dip aligning with biological development (Vijayakumar et al, ). These change patterns in working memory development could manifest in other areas such as decreased school engagement, increased conduct difficulties, and risk‐taking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Vijayakumar et al, 2014). These change patterns in working memory development could manifest in other areas such as decreased school engagement, increased conduct difficulties, and risk-taking behaviour.…”
mentioning
confidence: 99%